Occupational and Environmental Health Hazards among Agriculture Laborers: An Evidence-Based Study from Punjab, Pakistan - Jamshed, Farhat; Arshad, Muhammad; Afzal, Afzaal; Khalid, Maryam (Qlantic Journal of Social Sciences and Humanities, 2024)
Laborers from the agriculture sector have often been victims rather than beneficiaries of the green revolution, technological development, and globalization trends that characterized the 20th century. In recent decades, the laborers working in the agriculture sector have been half of the world’s labor force, with an estimated number of 1.3 billion worldwide, and a majority of them found in developing countries. Adequate balance between agricultural growth and protection from occupational & environmental health hazards is very crucial for the future of the world’s food production and for the sustainability of the sector. The study was conducted in three divisions of Punjab, and primary data was collected through multistage simple random sampling techniques. The interview schedule was used as a tool for data collection. The results revealed that the occupational and environmental circumstances of the laborers were not conducive towards their health and well-being. The agricultural laborers have to face many health hazards, whereas the majority of the laborers were exploited only due to their illiteracy and ignorance about Government policies and laws related to them. A huge proportion of the participants reported chronic health, malnutrition, and socio-economic problems significantly associated with their working environment, amenities and available facilities.